Voltage-dependent gating of KCNH potassium channels lacking a covalent link between voltage-sensing and pore domains - Lörinczi, Éva (Nature Pub. Group, 2015)
Voltage-gated channels open paths for ion permeation upon changes in membrane potential, but how voltage changes are coupled to gating is not entirely understood. Two modules can be recognized in voltage-gated potassium channels, one responsible for voltage sensing (transmembrane segments S1 to S4), the other for permeation (S5 and S6). It is generally assumed that the conversion of a conformational change in the voltage sensor into channel gating occurs through the intracellular S4–S5 linker that provides physical continuity between the two regions. Using the pathophysiologically relevant KCNH family, we show that truncated proteins interrupted at, or lacking the S4–S5 linker produce voltage-gated channels in a heterologous model that recapitulate both the voltage-sensing and permeation properties of the complete protein. These observations indicate that voltage sensing by the S4 segment is transduced to the channel gate in the absence of physical continuity between the modules.